Factors predicting health-related quality of life of the Malaysian B40 school-aged children living in urban poor flats in the central region of Malaysia - Cheah, Mun Hong Joseph; Chin, Yit Siew; Abu Saad, Hazizi; Lim, Poh Ying; Chan, Yoke Mun; Mohd Shariff, Zalilah (H E C Press, 2022)
Background and Objectives: Health-related quality of life (HRQoL) is a multidimensional concept that indicated an individual’s holistic health, whereby the urban-poor community are susceptible to low HRQoL due to their high vulnerability. This study aimed to determine factors that predicted the HRQoL among the urban-poor school-aged children. Methods and Study Design: This is a cross-sectional study and a total of 408 primary school-aged children (male: 72.3%; female: 27.7%), with a mean age of 9.68±1.48 years, were recruited from 10 urban-poor flats through cluster sampling at the central region of Malaysia. Their anthropometry, nutrition knowledge, attitude and practice, physical activity, dietary practices, and HRQoL were assessed. Results: A quarter (24.5%) of the urban-poor children were either overweight or obese in the present study. The HRQoL total score among the urban-poor children was 65.0±18.5. The result of multiple linear regression analysis shown that higher nutrition attitude (B=0.34, p=0.001) and practices (B=0.39, p=0.001), higher physical activity (B=3.73, p=0.004), higher lunch intake (B=1.35, p<0.001), lower supper intake (B=-1.35, p<0.001), and lower fast-food intake (B=-1.61, -1.17, p<0.001) are the significant predictors of better HRQoL among the urban-poor children (R2=0.32, F(8,399)=23.72, p<0.001). Conclusions: Future studies should focus on these predictors to formulate interventions that could enhance the HRQoL among the Malaysian urban-poor children.